A six month high resolution 4D geospatial stationiary laser scan dataset of the Kijkduin beach dune system, The Netherlands [dataset] - Vos, Sander; Anders, Katharina; Kuschnerus, Mieke; Lindenbergh, Roderik; Höfle, Bernhard; Aarninkhof, Stefan; de Vries, Sierd (PANGAEA - Data Publisher for Earth & Environmental Science, 2021)
Vos, Sander; Anders, Katharina; Kuschnerus, Mieke; Lindenbergh, Roderik; Höfle, Bernhard; Aarninkhof, Stefan; de Vries, Sierd (2021): A six month high resolution 4D geospatial stationiary laser scan dataset of the Kijkduin beach dune system, The Netherlands [dataset]. PANGAEA, https://doi.org/10.1594/PANGAEA.934058